Looking Back To Old, Forgotten Antibiotics to Treat Gram Negative Superbugs (International Journal of Emerging Trends in Science and Technology, 2017)
Antibiotic resistance has emerged as one of the greatest global health challenges to be addressed in the 21stcentury.The reintroduction of previously used antibiotics active against extensively drug-resistant (XDR)bacteria represents a new alternative for the control of antimicrobial resistance. A total of 100 extensivelydrug resistant Gram negative bacilli isolated from Clinical Microbiology laboratory.Acinetobacter wasfound to be the most common and highly resistant organism in this study (54%), which was isolated mostlyfrom respiratory and pus samples.Other extensively drug resistant Gram negative bacilli isolated fromClinical samples includes Klebsiella (33%) and Pseudomonas(13%).From the 100 Extensively drugresistant gram negative bacteria, the most common respiratory pathogen Acinetobacter shows 78%sensitivity towards Minocycline followed by Klebsiella (21%). Pseudomonas shows complete resistancetowards this drug.The old antibiotic Fosfomycin was active against all three species (Acinetobacter 94%,Klebsiella 100% and Pseudomonas 77%).Chloramphenicol shows less sensitivity towards Klebsiella (33%)and Acinetobacter(22%) and pseudomonas(16%).97% isolates were sensitive to polymyxins\colistin.